Reduced ADAMTS13 in children with severe meningococcal sepsis is associated with severity and outcome - Bongers, Tamara N.; Emonts, Marieke; de Maat, Moniek P. M.; Groot, Ronald de; Lisman, Ton; Hazelzet, Jan A.; Leebeek, Frank W. G. (Thrombosis and Haemostasis, 2010)
Multiple organ failure is a common feature of pediatric meningococcal sepsis and is associated with an imbalance of coagulation and fibrinolysis. This is partly due to an increased secretion of prothrombotic ultra-large von Willebrand factor (VWF) as the result of vascular endothelial damage. Another factor that may contribute is ADAMTS13, which converts VWF into smaller, less active, VWF multimers and thus influences VWF activity in plasma. We investigated the role of ADAMTS13 and VWF in the severity and outcome of sepsis. In 58 children with severe meningococcal sepsis we measured ADAMTS13 activity and antigen, VWF collagen binding activity (VWF:CB) and antigen levels (VWF:Ag), VWF propeptide and factor VIII at different time points during their stay in the paediatric intensive care unit. In the acute phase, both ADAMTS13 activity and antigen were decreased (median 23.4% and 33.7% of normal, respectively) and VWF:CB and VWF:Ag levels were strongly increased (325% and 348%, respectively.) ADAMTS13 antigen (23.9% vs. 34.6%; p=0.06) and VWF:CB (240% and 340% p<0.001) were lower in non-survivors than in survivors. ADAMTS13 activity and VWF:CB were both correlated with the severity of the disease, as indicated by the Pediatric Risk of Mortality score (Rs= –0.38 and Rs= –0.50, p=0.01, respectively, p<0.001). In the acute phase of severe sepsis decreased levels of ADAMTS13 and increased levels of VWF are observed, and the changes are related to severity of disease and outcome. This may contribute to the formation of microthrombi and the severity of thrombotic sequelae of sepsis.
Keywords: ADAMS/ADAMTS 13; disseminated intravascular coagulation (DIC); fibrinolytic disorders; paediatric haemostasis; sepsis